2013
DOI: 10.1371/journal.pone.0072732
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Effects of Genetic Variants within Th1 and Th17 Cell-Mediated Immune Response Genes on the Risk of Developing Rheumatoid Arthritis

Abstract: The present study was conducted to explore whether single nucleotide polymorphisms (SNPs) in Th1 and Th17 cell-mediated immune response genes differentially influence the risk of rheumatoid arthritis (RA) in women and men. In phase one, 27 functional/tagging polymorphisms in C-type lectins and MCP-1/CCR2 axis were genotyped in 458 RA patients and 512 controls. Carriers of Dectin-2 rs4264222T allele had an increased risk of RA (OR = 1.47, 95%CI 1.10–1.96) whereas patients harboring the DC-SIGN rs4804803G, MCP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
11
1
Order By: Relevance
“…We thus tested for a correlation between the relative abundance of fungal taxa associated with the disease phenotype (Basidiomycota and Ascomycota phyla as well as S. cerevisiae and M. sympodialis species) and the Card9 SNPs associated with IBD as well as several other SNPs that have been involved in defective responses to fungi. 12 19–23 We used standard linear regression and adjusted all analyses for age, gender, smoking and treatment. With a total of 84 tests, the Bonferroni corrected p value threshold for an initial alpha of 5% was 6×10 −4 .…”
Section: Resultsmentioning
confidence: 99%
“…We thus tested for a correlation between the relative abundance of fungal taxa associated with the disease phenotype (Basidiomycota and Ascomycota phyla as well as S. cerevisiae and M. sympodialis species) and the Card9 SNPs associated with IBD as well as several other SNPs that have been involved in defective responses to fungi. 12 19–23 We used standard linear regression and adjusted all analyses for age, gender, smoking and treatment. With a total of 84 tests, the Bonferroni corrected p value threshold for an initial alpha of 5% was 6×10 −4 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, gender-specific genetic effects have been observed in other traits [ 15 , 16 ]. In this study, our results suggested that the genetic variant located at 33 kb 5′ of LOC100506035 gene was associated with HM in a gender-specific way.…”
Section: Discussionmentioning
confidence: 99%
“…How environmental exposure to pathogens and danger signals affects the development of PBC is unclear, but epigenetics may play a role in activating and suppressing immune function genes . Finally, the Treg/Th17 balance seems to be more skewed towards Th17 in females than in males …”
Section: Female Preponderancementioning
confidence: 99%